El autonomismo en el sistema de partidos en Puerto Rico: Inercia institucional e ideología hegemónica (2008)
Political subordination in Puerto Rico seems to display some type of path dependency, a kind ofinertia that shows the importance of institutions in leading policies through the years. But, how do these institutions arise? And, why do they remain? A glance at the formation period of the emerging partysystem, allows to understand that it remained wrapped in the jumble of the metropolitan dynamic (Spanish first and American later) turning into a mere legitimizing instrument of dependency status. Political autonomy as an hegemonic ideology is the result of the interaction of forces and individuals with the interference of institutions that have limited the establishment of new political patterns. These institutional constraints have promoted the current static balance.